Modern Municipal Statutory Frameworks in Canada - Garcea, Joseph (Revue Gouvernance / Governance Review, 2004)
In this article, the author explains and assesses the modern municipal statutory frameworks in Canada. More specifically he examines the novel provisions that provincial and territorial governments are including in some of the emerging municipal statutory frameworks. The overarching purpose of such novel provisions is to supplant the restrictive features the traditional municipal statutory frameworks with permissive and empowering features. Such novel provisions include recognition of municipal governments as ‘orders of government’, ‘spheres of jurisdiction’, and ‘natural person powers’, as well as broader corporate powers and broader bylaw making powers. The author concludes that although the novel provisions constitute important steps in the right direction, they do not constitute a panacea either for municipal governments or, more importantly, for municipal governance. Indeed, he suggests that there is the potential for some negative ramifications for both if such novel provisions are not adopted and implemented with due care and attention to important matters such as the organizational capacity of various types of municipal governments to use them appropriately for various governance purposes.